Biochemical and biological evaluation of gyroxin isolated from Crotalus durissus terrificus venom - Barros, L. C. [UNESP]; Soares, A. M.; Costa, F. L.; Rodrigues, V. M.; Fuly, A. L.; Giglio, J. R.; Gallacci, Marcia [UNESP]; Thomazini-Santos, I. A. [UNESP]; Barraviera, Silvia Regina Catharino Sartori [UNESP]; Barraviera, Benedito [UNESP]; Ferreira Júnior, Rui Seabra [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Gyroxin, a thrombin-like enzyme isolated from Crotalus durissus terrificus venom and capable of converting fibrinogen into fibrin, presents coagulant and neurotoxic activities. The aim of the present study was to evaluate such coagulant and toxic properties. Gyroxin was isolated using only two chromatographic steps - namely gel filtration (Sephadex G-75) and affinity (Benzamidine Sepharose 6B) -resulting in a sample of high purity, as evaluated by RP-HPLC C2/C18 and electrophoretic analysis that showed a molecular mass of 30 kDa. Gyroxin hydrolyzed specific chromogenic substrates, which caused it to be classified as a serine proteinase and thrombin-like enzyme. It was stable from pH 5.5 to 8.5 and inhibited by Mn(2)+, Cu(2)+, PMSF and benzamidine. Human plasma coagulation was more efficient at pH 6.0. An in vivo toxicity test showed that only behavioral alterations occurred, with no barrel rotation. Gyroxin was not able to block neuromuscular contraction in vitro, which suggests that its action, at the studied concentrations, has no effect on the peripheral nervous system.
Keywords: gyroxin; neurotoxicity; coagulant activity; Crotalus durissus terrificus; serine proteinase